Effects of dietary sodium butyrate on growth performance, immune function, and intestinal microflora of Chinese soft-shelled turtle (Pelodiscus sinensis) - Ge, Lingrui; Yu, Yi; Wen, Xingxing; Xiao, Hewei; Liu, Kejun; Liu, Zhuying; Liu, Shuai; Li, Qian; Wang, Xiaoqing; Deng, Zaofu; Hu, Yazhou (Frontiers in Cellular and Infection Microbiology, 2023)
The Chinese soft-shelled turtle (Pelodiscus sinensis) has become increasingly susceptible to frequent diseases with the intensification of farming, which severely impacts the development of the aquaculture industry. Sodium butyrate (SB) is widely used as a feed additive due to its promotion of growth, enhancement of immune function, and antioxidative properties. This study aimed to investigate the effects of dietary SB on the growth performance, immune function, and intestinal microflora of Chinese soft-shelled turtles. A total of 300 Chinese soft-shelled turtles (mean weight: 11.36 ± 0.21g) were randomly divided into four groups with three parallel sets in each group. Each group was fed a diet supplemented with 0%, 0.005%, 0.01%, or 0.02% SB for 60 days. The results demonstrated an upward trend in weight gain rate (WGR) and specific growth rate (SGR) with increasing SB supplementation, and the experimental group fed with 0.02% SB showed a significant increase in WGR and SGR compared to other groups (P< 0.05). These levels of SB also decreased the levels of feed conversion ratio (FCR) and the total cholesterol (TC) content of Chinese soft-shelled turtles, and the 0.02% SB was significantly lower than that of other groups (P< 0.05). The activity of complement protein in vivo increased with increases in SB content, and the activities of complement C3 and C4 reached the highest level with 0.02% SB. The species abundance of the experimental group D fed with 0.02% SB was significantly higher than that of other groups (P< 0.05). Furthermore, the relative abundance of Clostridium sensu stricto 1 was significantly increased with 0.02% SB (P< 0.05). In conclusion, adding 0.02% SB to the diet improves the growth performance, feed digestion ability, and intestinal microbiota of Chinese soft-shelled turtles.